Sports nutrition in canoeing - Garcia Soidan, J. L. (Training sprint canoeing. Progress in improving the physical, technical, tactical, psychological and nutritional preparation, 2015)
Many times vve see how valid theoretical approaches fail to demonstrate the desired benefits and other times, unfortunately, we see how the popular use of certain substances lacks foundation. Sports drinks and energy bars are useful in training or strengthcompetition among the canoeists, immediately before, during and after that test or training, which aims to ensure maximum muscle and liver glycogen and electrolytes concentration. Regarding fats we must note that if resistance training saves the consumption of carbohydrates, increasing an intake of lipids, ingesting latter would save glycogen and consequently improve performance. However, what is causing a fat overload is a decrease in performance, in addition to the associated risks of obesity and cardiovascular disease. Other lipid substances that have failed to demonstrate their ergogenic potential are: medium chain triglycerides, glycerol, the smilax, gamma-orizanol and telluric acid. Regarding the latter, recent researches indicate that it inc roast's levels of endorphins, thus reducing the perception of fatigue in the canoeist.